Economic contributions of the Ottoman Bank in the Ottoman Empire and the Turkish Republic - Şenel, Seçil (Springer, 2018)
The Ottoman Bank had a special place in the Ottoman Empire during the development of monetary and credit institutions. Founded in 1863, the Ottoman Bank functioned as the central bank for many subjects in the Ottoman Empire, and the bank is an interesting example of the role of foreign capital control over finance and the economy. The Ottoman Bank handled treasury operations until the establishment of the Central Bank and continued to protect the state bank statue. In this chapter, the duties and economic effects of the Ottoman Bank, which started in the Ottoman Empire and continued in the Republic of Turkey, will be discussed in the historical process.
WOS: 000444369900013
Keywords: History of Economics; Economy; Ottoman Bank; Turkish Economy; Ottoman Empire